LATE RENAL GRAFT REJECTION: PATHOLOGY AND PROGNOSIS - E.S. Stolyarevich; L.Y. Artyukhina; I.G. Kim; L.G. Kurenkova; N.A. Tomilina (Вестник трансплантологии и искусственных органов)
Rejection has always been one of the most important cause of late renal graft dysfunction. Aim of the study was to analyze the prevalence of different clinico-pathological variants of rejection that cause late graft dysfunction, and evaluate their impact on long-term outcome. Materials and methods. This is a retrospective study that analyzed 294 needle core biopsy specimens from 265 renal transplant recipients with late (48,8 ± 46,1 months after transplantation) allograft dysfunction caused by late acute rejection (LAR, n = 193) or chronic rejection (CR, n = 78) or both (n = 23). C4d staining was performed by immunofl uorescence (IF) on frozen sections using a standard protocol. Results. Peritubular capillary C4d deposition was identifi ed in 36% samples with acute rejection and in 62% cases of chronic rejection (including 67% cases of transplant glomerulopathy, and 50% – of isolated chronic vasculopathy). 5-year graft survival for LAR vs CR vs their combination was 47, 13 and 25%, respectively. The outcome of C4d– LAR was (p < 0,01) better than of C4d+ acute rejection: at 60 months graft survival for diffuse C4d+ vs C4d− was 33% vs 53%, respectively. In cases of chronic rejection C4d+ vs C4d– it was not statistically signifi cant (34% vs 36%). Conclusion. In long-term allograft biopsy C4d positivity is more haracteristic for chronic rejection than for acute rejection. Only diffuse C4d staining affects the outcome. C4d– positivity is associated with worse allograft survival in cases of late acute rejection, but not in cases of chronic rejection.